2018
DOI: 10.3390/f9030101
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Bark Beetle Outbreaks, Salvage Logging and Wildfire Restructure a Lodgepole Pine Ecosystem

Abstract: Abstract:The 2010 Church's Park Fire burned beetle-killed lodgepole pine stands in Colorado, including recently salvage-logged areas, creating a fortuitous opportunity to compare the effects of salvage logging, wildfire and the combination of logging followed by wildfire. Here, we examine tree regeneration, surface fuels, understory plants, inorganic soil nitrogen and water infiltration in uncut and logged stands, outside and inside the fire perimeter. Subalpine fir recruitment was abundant in uncut, unburned,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Nonetheless, under some circumstances, salvage logging can meet both management and conservation objectives and address societal concerns. For example, salvage logging after bark beetle infestation of lodgepole pine forests in Colorado commonly reduces canopy fuels and regenerates new stands without negatively affecting native plant diversity or soil productivity (Collins et al 2011(Collins et al , 2012Fornwalt et al 2018;Rhoades et al 2018). As a consequence, controversy surrounding salvage logging among managers, environmentalists, politicians, and academics remains lively (Schiermeier 2016;Lindenmayer et al 2017;Müller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, under some circumstances, salvage logging can meet both management and conservation objectives and address societal concerns. For example, salvage logging after bark beetle infestation of lodgepole pine forests in Colorado commonly reduces canopy fuels and regenerates new stands without negatively affecting native plant diversity or soil productivity (Collins et al 2011(Collins et al , 2012Fornwalt et al 2018;Rhoades et al 2018). As a consequence, controversy surrounding salvage logging among managers, environmentalists, politicians, and academics remains lively (Schiermeier 2016;Lindenmayer et al 2017;Müller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors argue that ecological responses to salvage logging may result in synergistic effects due to the two successive disturbance events (the natural disturbance and then logging) occurring close in time (Van Nieuwstadt et al 2001;Wohlgemuth et al 2002;Karr et al 2004;Lindenmayer et al 2004;DellaSala et al 2006;Lindenmayer and Noss 2006). Others have found that environmental drivers other than salvage logging are more important in determining ecosystem regeneration (Kramer et al 2014;Peterson and Dodson 2016;Royo et al 2016;Rhoades et al 2018). Further, studies often report contradictory results, and there is currently no comprehensive, global assessment of the studies that have addressed salvage logging effects on ecosystem processes.…”
Section: Introductionmentioning
confidence: 99%
“…; Rhoades et al . ). Regardless, salvage logging can generate trade‐offs between ecological and fuel‐reduction objectives; for example, reducing the amount of dead wood can help meet fuel‐reduction goals but eliminate important habitat features for certain taxa (Thorn et al .…”
mentioning
confidence: 97%
“…Many forest ecosystems are subject to interacting disturbances that may affect ecological condition, biodiversity and ecosystem processes (e.g. Barlow et al., 2018; Cochrane & Barber, 2009; Rhoades, Pelz, Fornwalt, Wolk, & Cheng, 2018; Zald & Dunn, 2017). Mountain Ash forests are an example of such an ecosystem and work in them to date provides lessons for managing other highly disturbed forest ecosystems worldwide (Watson et al., 2018).…”
Section: Lessons For Managing Multiple Interacting Disturbancesmentioning
confidence: 99%